The relationship between national and international jurisdiction for ‘core crimes’ under international law-a critical analysis - Wibabara, Charity (2014)
Magister Legum - LLM === With regard to the establishment of legislative frameworks for investigating and prosecuting genocide, crimes against humanity and war crimes at both national and international level, a number of pertinent issues come up concerning the Court which should have primacy to deal with a particular case. States have had a variety of options at their disposal, such as complementarity, exclusivity, subsidiarity and concurrent jurisdiction principles. As a rule, these experiences find their limits in the full criminalisation of conduct that is also punishable before the international criminal tribunals under international law, ignoring the fact that international law does not provide definite guidance with respect to a number of questions in relation to interaction between national and international jurisdiction vis-à-vis the ‘core crimes.’ In addition,a considerable increase in the content of international law and divergences in various legal systems in criminal law, both general and special, since the end of World War II, influence the effective prosecution of ‘core crimes.’ Against this background; this work is organised into five chapters. Chapter one gives a general introduction and background to the study. Chapter two will set out the present international legal framework governing the prosecution of ‘core crimes’ in national courts and a description of the relevant practice in various states. Chapter three will examine critically the jurisdiction and overlaps of the international courts and ad hoc tribunals,along with the corresponding models of international criminal justice of exclusivity, subsidiarity, complimentarity and concurrent jurisdiction. Chapter four seeks to discuss the optimal relationship based on interactions between national and international jurisdictions. It will also include the merits and limits of both jurisdictions, basing on existing precedents and legislation.Finally, Chapter five contains a summary of conclusions drawn from the whole study and winds up with a set of recommendations.